Retelling Strategy towards Students’ English Reading Comprehension at Senior High Schools - Rudiawan, Rudiawan; Jupri, Jupri (JOLLT Journal of Languages and Language Teaching, 2020)
It was found that the majority of the students felt reluctant, nervous, and shy to read, especially when they were asked to read in front of their friends. The research objective is to find out how the use of the retelling-based instruction strategy can increase the students’ reading comprehension and find out the participants’ perceptions on the Retelling as a technique used to improve their reading comprehension. This research was experimental research that deals with utilizing the independent variable (the retelling technique) toward learners’ reading comprehension. Fifty-two students were involved in this study. The XI-A class was taken as the experimental class, and XI-B was treated as the control class. The research shows that it is significantly different in teaching English by using a retelling strategy to improve the students’ reading comprehension. The sig. (2-tailed) is 0.000 is lower than the significant level (0.05). Thus, the retelling strategy can improve the students’ reading comprehension in SMAN 1 Jonggat, Praya, Central Lombok. The t-test is higher than the t-table, 8.04 < 1.67. This also certainly concludes that there is a significant difference in teaching reading by using retelling strategy and not using retelling strategy. There is a positive contribution to the teaching of English reading comprehension by using retelling strategy in the SMAN 1 Jonngat, Praya, Central Lombok. All 25 students in the experimental class were happy and enjoyed reading by using the retelling strategy.